The potential of gardening and other plant‐related interventions to reduce symptoms of depression: A systematic review of non‐randomized controlled trials and uncontrolled studies - Claudio D. Rosa; Talisson S. Chaves; Silvia Collado; Lincoln R. Larson; KangJae Jerry Lee; Christiana C. Profice (People and Nature)
Abstract Previous systematic reviews have examined the effect of horticultural interventions (e.g., taking care of plants, planting, gardening) on individuals' depressive symptoms through analyses focused exclusively on randomized controlled trials, but that approach overlooks a majority of the potentially informative published research. To complement previous work, we searched the databases MEDLINE, PsycArticles, SCOPUS, Google Scholar, and ClinicalTrials.gov and identified 30 non‐RCTs (n = 1063 participants; all adults) and 32 uncontrolled studies (n = 517 participants; only one study included 6 young people) examining the effects of horticultural interventions on depression. Using random effects meta‐analysis, we discovered the evidence from these studies largely supports findings from RCTs. Like the RCTs, the non‐RCTs indicate that some horticultural interventions combined with usual care (i.e., continuing normal routine for healthy people or conventional treatment for unhealthy ones) may reduce depressive symptoms more than usual care alone, with most studies finding a moderate (Hedges' g ≥ 0.5) or large effect (g ≥ 0.8). We also found that participants might adhere similarly well or even better to horticultural interventions than to usual care alone, and no adverse events were reported. Twenty‐five of the 32 uncontrolled studies reported pre and post‐intervention mean depression scores. Of these 25 studies, 24 reported an improvement in mean depression scores and, in 16 of them, the improvement was greater than 20%. All studies present some risk of bias due to design limitations, but no evidence of publication bias was detected. Our findings support assertions that some horticultural interventions are effective and safe as a complementary strategy to reduce adults' depressive symptoms. More research is needed to understand how specific participant and intervention characteristics can influence the success of horticultural interventions on depressive symptoms. Read the free Plain Language Summary for this article on the Journal blog.